Production of rhamnolipids by pseudomonas aeruginosa AP029-GLVIIA and application on bioremediation and as a fungicide - Santos, Everaldo Silvino dos (2021)
Rhamnolipids are biosurfactants synthesized by different species of microorganisms. In this study, the influence of carbon/nitrogen ratio (C/N) and percentage of inoculum onrhamnolipid production by Pseudomonas aeruginosa AP029-GLVIIA using glucose as substrate was evaluated. The critical micellar concentration (CMC) and surface tension were analyzed for the highest biosurfactant concentration, which presented values of 49.63 mg/L and 29.5 mN/m, respectively. Emulsification rates were determined for different solvents and showed the bioproduct’s ability to form stable emulsions for up to 90 days. The efficiency of the biosurfactant in removing petroleum present in the sand was 16.8%and the antimicrobial activity of the rhamnolipid against fungal species was determined, showing its potential to inhibit fungi of the species Candida tropicalis and Candida albicans